The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11250-010-9637-8
|View full text |Cite
|
Sign up to set email alerts
|

Viability of cattle sperm under different storage conditions in Cameroon

Abstract: A study was carried out to evaluate the viability of extended cattle semen, without freezing, under different storage conditions. The semen was collected from Holstein Friesian bulls using artificial vaginas. The semen was extended and stored in a 3-by-4 factorial design (storage system × ice change). The storage media were ice boxes, buckets, and refrigerator. The ice in these media was either replaced daily, on the first and third day, first day only, or no ice at all after the semen collection. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
3
0
3
Order By: Relevance
“…On the other hand, we evaluated the kinetic motilities of frozenthawed semen into three different times: results showed that time of evaluation did not differ between periods of evaluation i.e., the storage semen in frozen form at (-196°C) using liquid nitrogen will not change the kinetic values of sperm even stored for long period. This is in contrast with semen stored in chilled form even in different storage conditions (Bayemi et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, we evaluated the kinetic motilities of frozenthawed semen into three different times: results showed that time of evaluation did not differ between periods of evaluation i.e., the storage semen in frozen form at (-196°C) using liquid nitrogen will not change the kinetic values of sperm even stored for long period. This is in contrast with semen stored in chilled form even in different storage conditions (Bayemi et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Pengamatan motilitas mengikuti metode Garner dan Hafez (2008) dengan mengestimasi persentase pergerakan spermatozoa maju ke depan (progresif) yang dinilai oleh 2 orang lalu diambil rataratanya. Menurut Bayemi et al (2010) pengujian motilitas dilakukan dengan cara semen diteteskan pada gelas objek lalu ditutup menggunakan cover penutup selanjutnya diamati dengan mikroskop perbesaran 400x.…”
Section: Bahan Dan Metodeunclassified
“…The average maximum and minimum temperatures are respectively 25°C and 14°C. The average relative humidity is 52% in the dry seasons and 70% in the wet seasons [8].…”
Section: Description Of Study Sitementioning
confidence: 99%